Polymer networks based on photo-caged diene dimerization. Issue 1 (1st October 2018) - Krappitz, Tim; Feist, Florian; Lamparth, Iris; Moszner, Norbert; John, Hendrik; Blinco, James P.; Dargaville, Tim R.; Barner-Kowollik, Christopher
Abstract : The rapid self-dimerization of photochemically generated o -quinodimethanes is exploited for λ-orthogonal network formation. Abstract : A powerful, simple and efficient method for photochemical crosslinking, exploiting the self-dimerization of photo-caged dienes based on o -methylbenzaldehydes ( o -MBAs) is introduced. Using a small molecule model system it is possible to identify the intermediate and final products of this light induced dimerization process. The bi-functional photocurable monomers contain o -MBA as well as vinylic units, which enables radical copolymerization with other monomers to tune the mechanical properties of the resulting networks. Crosslinked materials with reduced E -moduli ranging from 0.29 to 5.76 GPa and a hardness between 52 and 329 MPa were obtained, thus spanning a wide regime of different 'soft' to 'hard' material properties. The functional groups can be addressed through simultaneous reaction or in a λ-orthogonal fashion. This orthogonality can be achieved by inducing the free radical polymerization independently of the dimerization either thermally or via photoinitiation at a wavelength higher than the wavelength used for the non-radical dimerization process (>400 nm). Critically, this allows for a spatially defined adjustment of both the E -modulus and hardness within the respective material by controlling the irradiation parameters, such as wavelength, curing time and intensity. The introduced self-dimerizing resists thus represent a highly controllable combined radical/non-radical and λ-orthogonal curing system.